IMPLEMENTASI LITERASI DIGITAL MELALUI BAHAN AJAR BERBASIS FOCUSKY PADA GURU SEKOLAH DASAR - Dadang Kurnia; Elly Sukmanasa; Fitri Siti Sundari; Asoka Niscaya Alam Mayang; Yasmine Anggara Fergiawan (Jurnal Pengabdian Masyarakat Ilmu Keguruan dan Pendidikan (JPM-IKP), 2024)
Responding to challenges in the world of education requires 21st century life skills where teachers are expected to be creative individuals, able to teach, educate, inspire. This activity aims to improve teachers' digital literacy skills in creating teaching materials through Focusky presentation media. The basis for assisting this activity includes (1) the limitations of teachers who do not yet have competence in creating media based on the industrial revolution 4.0 platform, (2) teachers still lack initiative or creativity in developing digital literacy-based teaching materials, (3) the limitations of schools in bringing in students. experts or experts who have mastered knowledge in the field of developing digital literacy-based teaching materials. Activities are carried out in two stages, namely training and guidance in making Focusky-based teaching materials. The results show that teachers at SDIT Utsmanil Hakim Tanah Sareal, Bogor City, have succeeded in improving their digital literacy skills and can create focusky-based teaching materials with good results so that they can improve the quality of their students' learning and share information about their experiences by making these material products through mass media